(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Forensic odontology is a fastly growing field in both dental and forensic sciences. It involves the application of principles and expertise of dental sciences for criminal investigations. With increasing demand and use of dental evidence in forensic examinations, proper knowledge and awareness of the subject is more necessary than ever before. Materials and Method: A survey was conducted in Medical and Dental colleges in and around Mangalore, Dakshina Kannada after approval from institutional ethics committee. It included MBBS and BDS students (III year to internship) Result: The analysis of the data showed two fold results. Knowledge of tooth as a source of DNA, evidence for natural disasters in personalle identification was equal among the graduates. Medical graduates had higher awarenes of certain aspects like barr bodies and anthropometry whereas; Dental graduates were aware of the odontology aspects in identification of cases of rapes, child abuse, techniques like forensic radiology, bite mark analysis and sexual dimorphism in teeth. Conclusion: The study highlighted the difference in knowledge of forensic odontology between medical and dental students. It emphasized on the need of increasing awareness of the subject among medical graduates and to help them understand the role of their peers from the dental fraternity in forensic sciences. The study also stressed on the need of a forensic odontologist in the State Forensic Team.